The Implementation of the Use of Seed Bag Panel Boards for Vegetable and Crop Farmers in Kopeng - Prajanti, Sucihatiningsh Dian Wisika; Bintari, Siti Harnina; Nugrahani, Rahina (Universitas Negeri Semarang, 2022)
One of the agricultural problems in the spotlight is the quality of harvest and postharvest commodities, which still needs to improve due to the failure of special handling. One solution for handling perishable and low-value agricultural commodities is to sell agricultural products alive and in special packaging on panel boards as wall decorations based on green interiors with an urban farming concept. The research aims to implement the concept of vegetable and flower panel boards based on green interiors to increase the marketing value of agricultural products in Kopeng. The application of this panel board concept is to improve the quality of agricultural products because they are easily damaged, so the public consumes fresh vegetables of good quality with this panel board. Three simultaneous benefits of panel boards are art, aesthetics and product freshness when consumed. The prototyping is panel board products with steps to ensure the concept's design, functionality and feasibility, panel size, layout of vegetables and flowers, panel placement and other supporting structures. Test the prototype by growing vegetables and flowers and storing fruit from user input. Prototypes that are refined and tested well are then developed into marketing strategies. This program is about applying the panel board concept to improve the quality of agricultural products by providing added value to agricultural products so that they can increase the profits received by farmers. From the implementation that has been carried out, marketing results have increased by 10% from marketing before using seed bags.